Naufragare per giardini : Straniamento e spaesamento nell’Isola Felsenburg di Johann Gottfried Schnabel - Ferragamo, Emmanuela (Incontri. Rivista europea di studi italiani, 2021)
A Shipwreck in the GardenEstrangement and Confusion in Utopic Landscape in Johann Gottfried Schnabel’s Isle FelsenburgThis essay analyses the description of the garden in the first volume of Isle Felsenburg (1731), a utopian novel by Johann Gottfried Schnabel. The paper aims to underline the central role of both ‘wonder’ and ‘estrangement’ in creating a utopian landscape by focusing on the garden of Albert Julius, patriarch of the community. While the beauty of the garden astonishes the narrator, it also results in estrangement, as it drives the reader away from the present into the creatural past of humankind, a lost Eden. Such estrangement is a form of displacement: the subject is incapable of finding its own place in nature.